USING CRUDE PALM OIL (CPO) AS DIESEL ENGINE FUEL - T.H. Lim; S. Bari; C.W. Yu (Universitas Gadjah Mada, 2002)
In this study, heating was used to lower the viscosity of CPO to an acceptable level. 60°C was found to be the optimum heating temperature for CPO to ensure smooth flow in the fuel system, but heating further up to 100°C did not improve the engine performance. A comparison between CPO and diesel in terms of engine performance, combustion characteristics and emission showed that the brake specific fuel consumprion (bsfc) for CPO was 13% higher at 400 kPa brake mean effective pressure (bmep), and the highest bmep achieved was 13.5% lower. However, CPO fuel gave a brake thermal efficiency. Combustion analyses indicated that CPO combustion produced a 7% higher peak pressure, a 3.3-degree earlier ignition and an 11.6-degree longer burning duration, but a 26% lower peak heat release rate. After 500 hours of running CPO, performance and power of the engine dropped even while running with diesel. With a 26% higher bsfc and a 20% lowe maximum bmep. Visual inspection of the dismantled engine parts discovered heavy carbon deposits but normal wear. Overhaul of the engine restored the power and performance.